Strategi Peningkatan Kreativitas Peserta Didik melalui Metode Berbasis Masalah dalam Pembelajaran PKn di MAN Sidoarjo - Yusantika, Friska Dwi (LP3M STITNU AL HIKMAH MOJOKERTO, 2022)
An inefficient learning process is the root of the problems in this study. MAN Sidoarjo's civics curriculum suggests that there hasn't been enough progress made in producing excellent, intelligent citizens. The present study aims to explicate the ways in which PBM implementation can augment learners' creativity. A qualitative approach combined with descriptive methodologies is the research methodology employed in this study. Teachers, students, and principals are among the research subjects. The methods included documentation, interviews, and observation in the data collection process. Data reduction, data visualization, and conclusion/verification were used in the analysis of the data. The results of this study showed that the application of PBM in Civics classes can boost students' creativity in a way that is related to the learning phases, including the introduction, major activities, and closing activity. Nonetheless, the learning approach is less inventive, and practically all of the resources are appropriate for Civics utilizing the PBM approach. As a result, when constructing PBM using the debate or discussion technique, teachers must find educational resources that are connected to the mind map.